Veterinary psychopharmacology - Crowell-Davis, Sharon L.; Murray, Thomas, 1946-; Dantas, Leticia Mattos de Souza (John Wiley & Sons, Inc., 2019)
"Offers an updated second edition of the comprehensive reference on the use of drugs for veterinary mental health care and behavior modification. This fully revised Second Edition of Veterinary Psychopharmacology offers an authoritative reference to the drugs prescribed to treat psychiatric, psychological, and behavioral disorders in pets. Designed to be an accessible resource, the text is divided into sections on psychopharmacologic principles and clinical psychopharmacology. Comprehensive in scope, the book contains detailed information on pharmacologic intervention for pet mental health and behavior issues, offers thorough explanations of options, and explores why a particular drug should be prescribed and why it works. Updated to include the recent advances in psychopharmacology for pets, the Second Edition includes new chapters that cover the principles of psychopharmacology, miscellaneous serotonergic agents, anticonvulsants and mood stabilizers, sympatholytic agents, and NMDA antagonists. In addition, the text explains the drug options, including all the information necessary to correct dysfunctions in the brain's chemistry through pharmacologic treatment. This important resource: Presents an updated and comprehensive resource for pharmacologic treatments for pet, equine, and zoo animal psychiatric disorders and behavior problems; Contains in-depth information on drugs that promote neurochemical changes that will alter the mood, emotional state, reactivity, and behavior of the patient, including prescribing options and mechanisms of action; Includes new chapters on the principles of psychopharmacology, miscellaneous serotonergic agents, mood stabilizers, sympatholytic agents, and NMDA antagonists. Written for veterinarians, veterinary behaviorists, and veterinary students, the updated second edition of Veterinary Psychopharmacology is a complete source for current knowledge on pharmacologic behavior modification"--Provided by publisher.